Empowering primary care workers to improve health services: results from Mozambique's leadership and management development program - Perry Cary (BMC, 2008)
Abstract This article is the third article in the Human Resources for Health journal's feature on the theme of leadership and management in public health. The series of six articles has been contributed by Management Sciences for Health (MSH) and will be published article-by-article over the next few weeks. The third article presents a successful application in Mozambique of a leadership development program created by Management Sciences for Health (MSH). Through this program, managers from 40 countries have learned to work in teams to identify their priority challenges and act to implement effective responses. From 2003 to 2004, 11 health units in Nampula Province, participated in a leadership and management development program called the Challenges Program. This was following an assessment which found that the quality of health services was poor, and senior officials determined that the underlying cause was the lack of human resource capacity in leadership and management in a rapidly decentralizing health care system. The program was funded by the US Agency for International Development (USAID) and implemented in partnership between the Mozambican Ministry of Health (MOH) Provincial Directorate in Nampula and Management Sciences for Health (MSH). The Challenges Program used simple management and leadership tools to assist the health units and their communities to address health service challenges. An evaluation of the program in 2005 showed that 10 of 11 health centers improved health services over the year of the program. The Challenges Program used several strategies that contributed to successful outcomes. It integrated leadership strengthening into the day-to-day challenges that staff were facing in the health units. The second success factor in the Challenges Program was the creation of participatory teams. After the program, people no longer waited passively to be trained but instead proactively requested training in needed areas. MOH workers in Nampula reported that the program's approach to improving management and leadership capacity at all levels promoted the efficient use of resources and empowered staff to make a difference.